Perception and use of herbal medicine by Indonesian Medical Doctors - Simatupang, Abraham; Widyawati, Tri; Susilaningsih, Neni; Tobing, Romauli; Kurniaty, Linggom; Silaban, Hertina; Djojosaputro, Mulyadi; Mahabuana, Bintang (Published by Universitas Gadjah Mada, 2025)
Indonesia has a long experience in traditional medicine such as jamu. The government has been encouraging all sectors, especially pharmaceutical industries together with research institutions and academia to increase herbal medicine research so that herbal medicine is increasingly used in health services, including by medical doctors. Various efforts have been made but empirically it seems that this goal has not been achieved. For this reason, it is necessary to conduct a survey to determine the understanding and use of herbal medicine among doctors. I was a cross-sectional study using an electronic questionnaire distributed to doctors who are members of the Indonesian Medical Association (IMA) per province. Three-hundred sixty-two respondents from 29 out of 38 (76%) provinces of Indonesia responded, and 263 out 362 respondents (72%) are general practitioners. In prescribing herbal medicines only 18.5% prescribed, 35% did not and 46.6% sometimes prescribed, respectively. Of the eleven phytopharmaceuticals/standardised herbal medicines only one medicine No. 5 was widely recognized by respondents (46.6%). This study showed that doctors' understanding of herbal medicine still needs to be improved through various means including webinars/seminars, journals that show good clinical trials so that they are more confident when prescribing herbal medicine to their patients. There is a need for more comprehensive information regarding the indications, efficacy and side effects of herbal medicine, through books or formularies that can be accessed by doctors. In addition, respondents agreed that herbal medicine should be taught in medical schools both in the pre-clinical and clinical phases.